2019
DOI: 10.1002/cap.10053
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of a Cemental Tear‐Associated Bony Defect Using Hyaluronic Acid and a Resorbable Collagen Membrane: A 2‐Year Follow‐Up

Abstract: Introduction:A cemental tear (CeT) is a special type of surface root fracture that may cause periodontal and even periapical tissue destruction. Unfortunately, there is limited knowledge as to how these rare cases can effectively be treated. The present case is believed to be the first reported in the literature treating a bony defect caused by a cemental tear with hyaluronic acid (HA) and a collagen membrane. The aim of this case report is to present a regenerative surgical approach with clinical and tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(60 citation statements)
references
References 13 publications
0
58
0
1
Order By: Relevance
“…The adjunctive application of HA on the surgical treatment of periodontal bone defects and mucogingival defects has shown promising results [ 12 , 18 , 19 , 20 , 21 ]. When applied as monotherapy or as adjunct to non-surgical periodontal therapy based on the aforementioned properties in promoting healing and regeneration, it has shown a positive, occasionally statistically significant, albeit generally moderate effect, on clinical parameters in favor of HA application [ 10 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adjunctive application of HA on the surgical treatment of periodontal bone defects and mucogingival defects has shown promising results [ 12 , 18 , 19 , 20 , 21 ]. When applied as monotherapy or as adjunct to non-surgical periodontal therapy based on the aforementioned properties in promoting healing and regeneration, it has shown a positive, occasionally statistically significant, albeit generally moderate effect, on clinical parameters in favor of HA application [ 10 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…After a full-thickness flap reflection, the defect was filled with HA followed by placement of the membrane. 2 years follow up CBCT revealed buccal plate reconstruction and bone fill in the periapical region proving that HA helped in wound healing and bone regeneration (30).…”
Section: Intrabony Defectsmentioning
confidence: 93%
“…Lin and co-workers studied 71 teeth with a confirmed diagnosis of cemental tear and found that the majority of these teeth presented with an abscess and swelling (66%), deep isolated periodontal pockets >6 mm (73%) and positive signs of pulp vitality (65%) (Lin et al, 2011). Vitality of the pulp usually remains unaffected by the presence of a cemental tear (Haney et al, 1992;Harrel & Wright, 2000;Leknes et al, 1996;Lin et al, 2010;Pilloni et al, 2019;Tulkki et al, 2006;Xie et al, 2017), unless the tooth had been previously misdiagnosed, leading to an unnecessary root canal treatment (Lin et al, 2011). Therefore, a vital pulp with concomitant periapical bone loss might indicate the possibility of a cemental tear (Lin et al, 2011;Tulkki et al, 2006), as periapical diseases of endodontic origin are usually associated with nonvital pulps with infected pulpal space (Bergenholtz, 1974).…”
Section: Clinical Presentation Of Cemental Tearsmentioning
confidence: 99%
“…Typical clinical features associated with cemental tears are gingival bleeding on probing (Damasceno et al, 2012;Lyons et al, 2005;Müller, 1999), swollen gingiva or alveolar mucosa (Blum et al, 2013;Haney et al, 1992;Lin et al, 2010;Ong et al, 2019;Park et al, 2018;Pilloni et al, 2019;Tai et al, 2007;Watanabe et al, 2012;Xie et al, 2017), purulent discharge through the periodontal sulcus or sinus tract (Blum et al, 2013;Camargo et al, 2003;Harrel & Wright, 2000;Leknes et al, 1996;Ong et al, 2019;Park et al, 2018;Schmidlin, 2012;Stewart & McClanahan, 2006;Tai et al, 2007;Watanabe et al, 2012;Xie et al, 2017), increased tooth mobility (Brunsvold & Lasho, 2000;Chawla & Kumar, 2019;Harrel & Wright, 2000;Müller, 1999;Nathani et al, 2021;Ong et al, 2019;Stewart & McClanahan, 2006;Watanabe et al, 2012;Xie et al, 2017) and a root filled tooth with post-treatment disease (Blum et al, 2013;Camargo et al, 2003;Chawla & Kumar, 2019;Damasceno et al, 2012;Jeng et al, 2018;Leknes et al, 1996;…”
Section: Clinical Presentation Of Cemental Tearsmentioning
confidence: 99%